Roles of GFAT and PFK genes in energy metabolism of brown planthopper, Nilaparvata lugens - Si, Hui-Ru; Sun, Si-Si; Liu, Yong-Kang; Qiu, Ling-Yu; Tang, Bin; Liu, Fang; Fu, Qiang; Xu, Cai-Di; Wan, Pin-Jun (Frontiers in Physiology, 2023)
Glutamine:fructose-6-phosphate aminotransferases (GFATs) and phosphofructokinase (PFKs) are the principal rate-limiting enzymes involved in hexosamine biosynthesis pathway (HBP) and glycolysis pathway, respectively. In this study, the NlGFAT and NlPFK were knocked down through RNA interference (RNAi) in Nilaparvata lugens, the notorious brown planthopper (BPH), and the changes in energy metabolism were determined. Knockdown of either NlGFAT or NlPFK substantially reduced gene expression related to trehalose, glucose, and glycogen metabolism pathways. Moreover, trehalose content rose significantly at 72 hours after dsGFAT injection, and glycogen content increased significantly at 48 hours after injection. Glucose content remained unchanged throughout the experiment. Conversely, dsPFK injection did not significantly alter trehalose, but caused an extreme increase in glucose and glycogen content at 72 h after injection. The Knockdown of NlGFAT or NlPFK significantly down-regulated the genes in the glycolytic pathway, as well as caused a considerable and significant decrease in pyruvate kinase (PK) activity after 48 h and 72 h of inhibition. After dsGFAT injection, most of genes in TCA cycle pathway were up-regulated, but after dsNlPFK injection, they were down-regulated. Correspondingly, ATP content substantially increased at 48 hours after NlGFAT knockdown but decreased to an extreme extent by 72 hours. In contrast, ATP content decreased significantly after NlPFK was knocked down and returned. The results have suggested the knockdown of either NlGFAT or NlPFK resulted in metabolism disorders in BPHs, highlighting the difference in the impact of those two enzyme genes on energy metabolism. Given their influence on BPHs energy metabolism, developing enzyme inhibitors or activators may provide a biological control for BPHs.